Kinerja Rantai Pasok Petani Kakao Mitra PT XYZ Area Operasional Kecamatan Palolo Kabupaten Sigi Sulawesi Tengah - Dinarsyah, Harkat; Handayani, Fani (Universitas Galuh, 2026)
The research used a case study method at one of the largest cocoa bean trading companies in Palolo District, namely PT XYZ. PT XYZ experienced several problems in the cocoa bean supply chain, including fluctuations in supply, low-quality cocoa beans from farmers, and delays due to competitors emerging. The purpose of this study was to analyze the supply chain performance of PT XYZ's partner cocoa farmers in the Palolo District operational area. The performance analysis was conducted using the Supply Chain Operations Reference (SCOR) approach and took into account internal and external attributes. The results of the study show that the average supply chain performance of partner farmers has reached superior levels in terms of assets, costs, standard compliance, order fulfillment cycle, and flexibility. Meanwhile, the performance indicator for deliveries by farmers is still categorized as advantageous.